Medición del Fotoperiodo en diferentes Latitudes y Altitudes de la Zona Tres - Suntaxi Criollo, Paúl David (2018)
The investigation was carried out in the zone three conformed by Cotopaxi, Chimborazo, Tungurahua, and Pastaza, the research was done with the objective of knowing the amount of light hours ("heliofania") that exist in different altitudes and latitudes of the zone, the hours monthly light obtained from May 2017 - April 2018, the data of light hours ("heliofania") of the communities of the Cotopaxi Province were obtained by the ArGis system, which provided data that were taken as reference for the realization of the investigation, the data obtained from the light hours at different latitudes and altitudes were divided into two seasons, winter and summer, which allowed a more detailed study. Two variables were evaluated: the amount of light hours present in different latitudes and the number of light hours present in different latitudes where the data were classified in different latitudes and altitudes according to the latitude and altitude where the meteorological stations and communities are located by season of the year summer (May 2017 and August 2018) and winter (November 2017 and April 2018) where the ranges represent the meteorological stations that are within them; according to the statistical analysis performed and when comparing the p-value, it was obtained that in different latitudes there is no significant difference in the months of the seasons (winter-summer) but in the summer season it presents two months where there was significance, July, and September, probably this is based on the climate of the season where cloudiness is the primary factor that influenced to present this variation, this is supported by Bernal, 2015 where it states that latitudes near the Equatorial line does not present difference in the light hours; on the other hand when evaluating the light hours according to the height, while performing the statistical analysis and comparing them with the p-value it is concluded that there is a significant difference and there is a difference in the hours light at a different height, this is collaborated by PARITARIOS, 2008, which shows that sectors located in the same area, atitude, there is no difference but this varies according to the height in which it is found, and this was demonstrated when performing the analysis of variance; in addition, the georeferencing of zone three was carried out where the geographical location of each one of the stations and communities of the Cotopaxi Province where the measurements of the light hours were taken.